Réécritures du mythe d’Orphée et enjeux esthétiques, philosophiques et formels dans The Mask of Orpheus de Harrison Birtwistle - Jean-Philippe Heberlé (Revue LISA)
This article deals with Harrison Birtwistle’s rewriting of the myth of Orpheus in his opera The Mask of Orpheus (1986). Written on a libretto by Peter Zinovieff, The Mask of Orpheus is part of a long tradition of operas dealing with the famous Greek myth. Yet, the way it is tackled by Birtwistle and Zinovieff is very different from what was done in the past. They do not present the spectator with the key elements of the story in a linear way but simultaneously. Different versions of the myth are introduced and sometimes we are presented with contradictory versions at the same time to force us to be active and aware of the existence of different kinds of dualities. The simultaneous presentation of some events is also connected to the way Birtwistle and Zinovieff play with the notion of time in their opera. One of their aims is to show how memory functions. When you remember something the frontier between past and present is blurred and the remembrance of things past is part of an endless cycle where things are perpetually brought to life, a very important aspect of myths whose universal and timeless nature is thus emphasized. Rituals, like myths, are based on the idea of repetition as well as on the idea of returning to the origins. This is why the opera may be considered as a ritualistic piece of work; this is underlined by the omnipresence of the figure three—a ritual number—in the literary and musical structure of The Mask of Orpheus.